2015
DOI: 10.1161/circ.132.suppl_3.16541
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 16541: Abnormal Brain Connectivity and Poor Neurodevelopmental Outcome in Congenital Heart Disease Patients With Subtle Brain Dysplasia

Abstract: Introduction: Mutant mouse models with congenital heart disease (CHD) were observed to have distinct brain dysplasia, prompting an assessment for brain anomalies in CHD patients. CHD infants with brain magnetic resonance imaging (MRI) assessments were recruited and scored using a novel brain dysplasia index. Validation was conducted with parallel brain connectome analysis and neurodevelopment outcome assessments. Methods: The Ohia mutant mouse line and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Conjointly, we found that these study participants with CHD also exhibited increased extra-axial CSF volume (qualitatively assessed) 3 . In a follow-up, albeit limited study, we showed that brain dysmaturation was associated with poor neurodevelopmental outcomes 52 , which has been supported by other studies as well 10,53…”
Section: Discussionsupporting
confidence: 81%
“…Conjointly, we found that these study participants with CHD also exhibited increased extra-axial CSF volume (qualitatively assessed) 3 . In a follow-up, albeit limited study, we showed that brain dysmaturation was associated with poor neurodevelopmental outcomes 52 , which has been supported by other studies as well 10,53…”
Section: Discussionsupporting
confidence: 81%
“…The BDS was based on previous correlative analysis of brain phenotype from CHD mouse mutant and human infant MRI including a spectrum of subtle brain dysplasia (hypoplasia or aplasia) including increased extra-axial CSF and abnormalities of the olfactory bulbs, cerebellum, hippocampus and corpus callosum and a composite brain dysplasia score, as previously described. 10, [30][31][32][33][34][35] Basic pediatric neuroradiological definitions and criteria were used from Barkovich et al for overall assessment of brain abnormalities. 55 For olfactory abnormalities, we assessed for aplasia/hypoplasia of the olfactory blub within the olfactory groove and aplasia/hypoplasia of the olfactory sulcus on high resolution coronal T2 images.…”
Section: Brain Dysplasia Score (Bds) Methodsmentioning
confidence: 99%
“…10, [30][31][32][33][34][35] This pattern of subcortical dysmaturation was predominantly seen in the olfactory bulb (dysmorphometry of left and right olfactory bulbs and sulci) , the cerebellum ( hypoplasia and/or dysplasia in cerebellar hemispheres and vermis) and the hippocampus (hypoplasia or malrotation) are components of a larger spectrum of structural abnormalities including extraaxial CSF fluid increases, corpus callosum abnormalities, choroid plexus abnormalities and brainstem dysplasia that we have recently observed in both human CHD patients and preclinical CHD mouse models. 10, [30][31][32][33][34][35] As such, we have derived a composite Brain Dysplasia Score (BDS) which was previously created with one point given for each positive finding in any of thirteen parameters including: hypoplasia in cerebellar hemispheres and vermis; dysplasia in cerebellar hemispheres and vermis; supratentorial extra-axial fluid; dysmorphometry of left and right olfactory bulbs and sulci; abnormalities in hippocampus and choroid plexus; malformation of corpus callosum; and brainstem dysplasia. 10, [30][31][32][33][34][35] There is little known about the relationship of these milder structural dysplastic abnormalities (relative to more gross brain malformation) to white matter connectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6–9] Increased CSF volume has been shown to be correlated with brain dysmaturation (i.e., dysplastic cortical and subcortical structures, decreased cortical and subcortical volumes, and decreased cortical thickness), as well as poor neurodevelopmental outcomes in preoperative neonates[10] and young children with CHD. [2,3,11]…”
Section: Introductionmentioning
confidence: 99%